Genetic variability and character association for growth and yield characters in Dolichos bean (Lablab purpureus var. typicus) under rainfed semi-arid conditions (Current Horticulture, 2024)
The genetic variability and character association were studied in 60 genotypes of dolichos bean (Lablab purpureus var. typicus L.) during 2018-2023 at Central Horticultural Experiment Station (ICAR- CIAH), Panchmahals (Godhra), Gujarat. A degree of  variation was observed for all characters. High Phenotypic Co-efficient of Variation (PCV) and Genotypic Co-efficient of Variation  (GCV) were recorded for primary branches/plant, number of pods/plant, Pod length, pod weight and pod yield/plant. The high PCV  and GCV were recorded for primary branches/plant, number of pods/plant, pod length, pod weight and pod yield/plant indicated  maximum variability in the genotypes. High heritability coupled with high genetic advance as per cent mean was observed for plant  height, number of primary branches/plant, number of pods/plant, pod length, pod girth, pod weight and pod yield/plant indicating  that these characters are controlled by additive gene action. Thus, selection for these characters will improve the yield. Pod yield/ plant exhibited positive and highly significant correlation with number of branches, number of pods/plant, pod length, pod girth,  pod weight at both genotypic and phenotypic levels. Hence these traits should be considered as important selection criteria for  improvement of pod yield/plant.
Keywords: GCV; PCV; Heritability; Association; Genotype